Study of The Implementation of Minimum Service Standards for Maternal Health Services in Magelang City - Sri Suwitri; Rani Pajrin; Yuni Kurniasih; Triantono (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Maternal health services are an essential component of public health systems and play a significant role in reducing maternal mortality. The implementation of Minimum Service Standards (MSS) is one of the government’s strategies to ensure the quality and accessibility of maternal health services at the regional level. This study aims to analyze the implementation of Minimum Service Standards for maternal health services in Magelang City. This research employed a qualitative approach with a socio-legal perspective. Data were collected through in-depth interviews, observations, focus group discussions, and literature review involving stakeholders related to maternal health services. The data were analyzed using data reduction, data presentation, and verification through triangulation techniques to ensure validity. The results show that the implementation of MSS for maternal health services in Magelang City generally meets the established indicators, including the availability of health facilities, health personnel, and maternal health service coverage. However, several aspects still require improvement, particularly the quality of services and the continued involvement of traditional birth attendants in the childbirth process. Socioeconomic factors such as poverty, education level, and social inequality also influence the effectiveness of maternal health services. Strengthening community education and improving service quality are necessary to support optimal implementation of MSS. In conclusion, although the implementation of maternal health MSS in Magelang City has largely met the required standards, improvements in service quality and equitable access remain essential to optimize maternal health outcomes.